Happiness and the Blank Page: Csikszentmihalyi's Flow in the Writing Classroom - Gina Briefs-Elgin (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
Redefining happiness to include encounters with difficulty helps students embrace rather than dread arduous writing tasks.